KEMAMPUAN MAHASISWA JURUSAN SASTRA INDONESIA UNIVERSITAS ANDALAS DALAM MERESPONS KAIDAH BAHASA INDONESIA PADA LAMAN UKBI.INFO - Ria Febrina; Sri Wahyuni (Universitas Andalas, 2019)
Ukbi.info a page that used to examine the ability of bahasa Indonesia. This page is provided as exercise tool before doing official UKBI test held by Badan Pengembangan Bahasa dan Perbukuan Republik Indonesia. This research is aimed to examine students’ ability of Indonesian Department University Andalas in responding bahasa Indonesia principle. Computational method is applied in this reseach that create ukbi.info web including 500 questions of bahasa Indonesia to give responses about the principles or compatible with UU. No. 50 2015 or General Guide of Indonesia Spelling (PUEBI). To know the result of test, each of participants will be given an account based on registered number, then they will observe and answer 25 questions for 25 minutes. In conclusion, the result of research shows that students’ ability at Indonesian Department University Andalas are on intermediate/middle rank (rank of high school students) and mediocre (rank of middle school students). This rank is not compatible with standardization of Badan Pengembangan Bahasa dan Perbukuan Republik Indonesia, that is excellent. Therefore, it is highly recommended to Head of Indonesian Department University Andalas to establish standardization for graduated students to reach excellent rank. The establishment of this standardization is organized by socializing ukbi.info page to whole Indonesian Department students University Andalas and target the graduated students to get excellent rank before completing their comprehensive tests.Keywords: students’ ability, bahasa Indonesia principle, ukbi.info page